An Ontology of Omnipresent and Omniscient Cameras: Changes to Telejournalism and the Ubiquity of Devices for Recording Reality - Martins, Maura (Brazilian journalism research, 2016)
The proliferation of technological devices that visually register the world has led to changes in the narrative formats of telejournalism. The various types of cameras used by television stations – surveillance, amateur, hidden and even professional ones - give broadcasters a plethora of strategies for reaching an audience who tend to dominate and distrust the well-known media languages. This paper presents a proposal for categorizing the cameras used in daily telejournalism in order to better understand the specifics of the phenomenon. Overall, all these cameras appear to be used for creating a realist aesthetic with low media interference.